Fundamentals of Fluid Mechanics / International Student Edition: Sixth Edition - Huebsch Wade W; Munson Bruce R; Okiishi Theodore H; Young Donald F (John Wiley And Sons, Inc, 2010)
This book is respected by professors and students alike for its comprehensive topical coverage, its varied examples and homework problems, its application of the visual component of fluid mechanics, and its strong focus on learning. Introduction, Fluid Statics, Elementary Fluid Dynamics - The Bernoulli Equation, Fluid Kinematics, Finite Control Volume Analysis, Differential Analysis of Fluid Flow, Dimensional Analysis and Similitude and Modeling, Viscous Flow in Pipes, Flow Over Immersed Bodies, Open-Channel Flow, Compressible Flow, Turbomachines, Computational Fluid Dynamics and Flow lab, Physical Properties of Fluids, Properties of the U.S. Standard Atmosphere, Compressible Flow Data for an Ideal Gas, Online Appendix List, Comprehensive Table of Conversion Factors, Video Library, Review Problems, Laboratory Problems, CFD Driven Cavity Example, Flow lab Tutorial and User's Guide, Flow lab Problems, Answers, Index, Video Index.